Risk Management and Digital Transformation in Organization from Managerial Perspective: A Qualitative Approach - Kenza BENNIS; Oussama CHWIKI; Khadija BENAZZI (Communications of International Proceedings, 2022)
This exploratory research study examines the interconnection between digital transformation and risk management. This study shows that digital transformation, perceived as a self-assessment experience of the organization's capabilities and an important learning opportunity, is certainly not limited to the simple technical task of implementing a technological tool. Rather, it is a change that certainly requires strong managerial support based mainly on risk management. The latter, increased through digital transformation experience. It is the main raw material for decision making, implementation of objectives and process management, towards new successful and solid business models.
Keywords: Risk management; digital transformation; change management.